Degradation model of the dynamic mechanical properties and damage failure law of sandstone under freeze-thaw action. Issue 132 (May 2020) - Luo, Yi; Qu, Dengxing; Wang, Gang; Li, Xinping; Zhang, Guang
Abstract: In the construction process of alpine regions, the construction zone is often subjected to blasting vibrations, heavy truck transportation vibrations, earthquakes and other dynamic loads. It is of great significance to analyse the dynamic mechanical properties of a rock mass under the coupling action of freeze-thaw cycles and dynamic loading. In this paper, the degradation laws of the static mechanical parameters and dynamic mechanical parameters and the failure modes of the sandstone are studied by static mechanical tests, electron microscopic tests and uniaxial impact compression tests on sandstone samples with different numbers of freeze-thaw cycles under impact loading. The test results show that the dynamic increase factor (DIF) is affected by the number of freeze-thaw cycles and the strain rate, and the strain rate is the dominant factor. For the dynamic increase factor of the elastic modulus DIFE, the effect of the strain rate on the DIFE is much smaller than that on the DIF, and the variation in the DIFE decreases with the increase in the number of freeze-thaw cycles. When the strain rate is constant, the dynamic compressive strength of the sandstone samples decreases exponentially with an increase in the number of freeze-thaw cycles. When the number of freeze-thaw cycles is constant, the dynamic compressive strength of the sandstone samples increases linearly with increasing strain rate. The dynamic compressive strength degradation model of sandstone considering the number of freeze-thaw cycles and strain rate is obtained by fitting the experimental data. In the early stage of the freeze-thaw cycle, the main dynamic failure mode of sandstone under the action of freeze-thaw cycles and a lower impact load is the axial splitting failure mode, while the dynamic failure mode of sandstone under freeze-thaw action and a higher impact load is the crushing failure mode. The research results can be used to predict the dynamic compressive strength of rock under different strain rates and varying numbers of freeze-thaw cycles and provide a theoretical basis for similar engineering construction. Highlights: The degradation mode of dynamic compressive strength of sandstone considering the number of freeze-thaw cycles and strain rate. The dynamic failure mode of sandstone under different number of freeze-thaw cycles and strain rate is different. The dynamic intensity factor DIF is affected by the combination of the number of freeze-thaw cycles and the strain rate.